Transcranial Doppler Waveforms During Intra-aortic Balloon Pump Counterpulsation for Vasospasm Detection After Subarachnoid Hemorrhage. Issue 3 (21st July 2017) - Morris, Nicholas A; Manning, Nathan; Marshall, Randolph S; Connolly, E Sander; Claassen, Jan; Agarwal, Sachin; Roh, David J; Schmidt, J Michael; Park, Soojin
Abstract: BACKGROUND: Transcranial Doppler ultrasound is a standard screening tool for vasospasm after subarachnoid hemorrhage. Prevention of vasospasm-induced delayed cerebral ischemia after subarachnoid hemorrhage depends on optimization of cerebral perfusion pressure, which can be challenged by neurogenic stress cardiomyopathy. Intra-aortic balloon pumps have been utilized to augment cerebral perfusion, but they change the transcranial Doppler waveform, altering its interpretability for vasospasm screening. OBJECTIVE: To assess the features of the transcranial Doppler waveform that correlate with vasospasm. METHODS: We retrospectively reviewed cases of subarachnoid hemorrhage that underwent same-day transcranial Doppler ultrasound and angiography. Transcranial Doppler waveforms were assessed for mean velocity, peak systolic velocity, balloon pump-augmented diastolic velocity, and a novel feature, "delta velocity" (balloon pump-augmented velocity − systolic velocity). Relationship of flow velocity features to vasospasm was estimated by generalized estimating equation models using a Gaussian distribution and an exchangeable correlation structure. RESULTS: There were 31 transcranial Doppler and angiography pairings (12 CT angiography/19 digital subtraction angiography) from 4 patients. Fourteen pairings had proximal vasospasm by angiography. Delta velocity was associated with proximal vasospasm (coefficient –6.8 [95% CI –9.8 to –3.8], P < .001). There was no significant correlation with proximal vasospasm for mean velocity (coefficient –13.0 [95% CI –29.3 to 3.4], P = .12), systolic velocity (coefficient –8.7 [95% CI –24.8 to 7.3], P = .29), or balloon pump-augmented velocity (coefficient –15.3 [95% CI –31.3 to 0.71], P = .06). CONCLUSION: Delta velocity, a novel transcranial Doppler flow velocity feature, may reflect vasospasm in patients with subarachnoid hemorrhage and intra-aortic balloon pumps.